1995
DOI: 10.1095/biolreprod52.6.1410
|View full text |Cite
|
Sign up to set email alerts
|

Production of viable bovine blastocysts in defined in vitro conditions

Abstract: Our purpose was to obtain viable blastocysts via in vitro maturation, fertilization, and culture (IVMFC) in serum- and BSA-free media (defined conditions) and to document viability by pregnancy initiation following embryo transfer (ET). Oocytes were matured in modified TCM 199 (mTCM 199) with 100 micrograms/ml ovine (o)LH, inseminated in TALP- or defined medium (DM)-based media, and cultured up to 9 days in synthetic oviductal fluid (SOF) prepared with 6 mg/ml polyvinyl alcohol (PVA) instead of BSA and buffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 41 publications
3
76
0
4
Order By: Relevance
“…In the present study, however, no beneficial effect of glutamine in combination with essential amino acids for basal medium Eagle (EAA-BME) and nonessential amino acids for minimum essential medium (NEAA-MEM) was observed even in the absence of glucose. This result supports the recent finding that the addition of 1 mM glutamine singly or in combination with EAA-MEM and/or NEAA-MEM, does not improve bovine embryo development [10,12,33]. Further experiments are needed to determine the optimal concentrations of glutamine for in vitro culture and its role in the development of bovine embryos, since it has been demonstrated that bovine embryos utilize glutamine as an energy source throughout their preimplantation development [25], and that the response of mouse embryos to glutamine depended on the concentration of NaCl in the culture medium [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, however, no beneficial effect of glutamine in combination with essential amino acids for basal medium Eagle (EAA-BME) and nonessential amino acids for minimum essential medium (NEAA-MEM) was observed even in the absence of glucose. This result supports the recent finding that the addition of 1 mM glutamine singly or in combination with EAA-MEM and/or NEAA-MEM, does not improve bovine embryo development [10,12,33]. Further experiments are needed to determine the optimal concentrations of glutamine for in vitro culture and its role in the development of bovine embryos, since it has been demonstrated that bovine embryos utilize glutamine as an energy source throughout their preimplantation development [25], and that the response of mouse embryos to glutamine depended on the concentration of NaCl in the culture medium [11].…”
Section: Discussionsupporting
confidence: 92%
“…The effects of glutamine and glycine on bovine embryonic development have been investigated by several groups, however, the supplementation of media with glutamine [10,12,20,23,33] or glycine [12,15,21,28] has given inconsistent results. One of the reasons is that the culture conditions used in these studies were variable: complex vs. simple media, with vs. without other amino acids, presence vs. absence of bovine serum albumin (BSA), and so on.…”
Section: Source Of Zygotesmentioning
confidence: 99%
“…Chemically defined conditions without serum or serum derived proteins allow more precise observation of effects of growth or other embryo growth factors in a given medium (Giles and Foote 1997;Sirisathien et al 2003;Oyamada et al 2004). It was demonstrated that chemically defined medium supported bovine zygote development to blastocysts with varying rates of success (Keskintepe et al 1995;Keskintepe and Brackett 1996;Lim et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Keskintepe et al, 1995;Takahashi et al, 1996;Matsui et al, 1997 , protein supplemen-Ž tation has been shown to be beneficial for embryo development in vitro Takahashi and . First, 1992;Carolan et al, 1995 .…”
Section: Introductionmentioning
confidence: 99%